Metagenome of Amazon forest conversion: impacts on soil-borne microbial diversity and functions - Mendes, Lucas William (2014)
The Amazon rainforest is considered the world\'s largest reservoir of plant and animal biodiversity, but in recent years has been subjected to high rates of deforestation for the conversion of native areas into agricultural fields and pasture. The understanding of the effects of land-use change on soil microbial communities is essential, taking into account the importance that these organisms play in the ecosystem. In this context, this thesis evaluated the effect of these changes on microorganism communities in soils under different land-use systems. In the first study, the microbial communities were analyzed using the nextgeneration sequencing Illumina Hiseq2000, considering samples from native forest, deforested area, agriculture and pasture. From the analysis of approximately 487 million sequences was possible to show that microbial communities respond differently in each landuse system, with changes in both taxonomic and functional diversity. Also, we suggested that ecosystem function in forest soils is maintained by the abundance of microorganisms, while in disturbed areas such functioning is maintained by high diversity and functional redundancy. In the second study, we assessed the extent to which a particular plant species, i.e. soybean, is able to select the microbial community that inhabits the rhizosphere. From the metagenomic sequencing by the 454 GS FLX Titanium platform we investigated the taxonomic and functional diversities of soil and rhizosphere communities associated to soybean, and also tested the validity of neutral and niche theories to explain rhizosphere community assembly process. The results suggest that soybean selects a specific microbial community inhabiting the rhizosphere based on functional traits, which may be related to benefits to the plant, such as growth promotion and nutrition. This process of selection follows largely the niche -based theory indicating the selection power of the plant and other environmental variables in shaping the microbial community both at the taxonomic and functional level. This thesis highlights the importance of microbial ecology studies in the context of the Amazon to a better understanding of the effects of deforestation on microorganisms, and provides information that can be suitable for future development of sustainable approaches for the ecosystem use